2016
DOI: 10.1038/tp.2016.225
|View full text |Cite
|
Sign up to set email alerts
|

Are adolescents more vulnerable to the harmful effects of cannabis than adults? A placebo-controlled study in human males

Abstract: Preclinical research demonstrates that cannabinoids have differing effects in adolescent and adult animals. Whether these findings translate to humans has not yet been investigated. Here we believe we conducted the first study to compare the acute effects of cannabis in human adolescent (n=20; 16–17 years old) and adult (n=20; 24–28 years old) male cannabis users, in a placebo-controlled, double-blind cross-over design. After inhaling vaporized active or placebo cannabis, participants completed tasks assessing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
103
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(113 citation statements)
references
References 88 publications
6
103
3
1
Order By: Relevance
“…Craving is stronger in more severe users and has been found to predict CUD problem severity , treatment outcome and withdrawal severity in heavy users. Craving generally decreases during intoxication , but adolescents may be less prone to these satiation‐induced decreases in craving .…”
Section: Clinical Representationmentioning
confidence: 99%
“…Craving is stronger in more severe users and has been found to predict CUD problem severity , treatment outcome and withdrawal severity in heavy users. Craving generally decreases during intoxication , but adolescents may be less prone to these satiation‐induced decreases in craving .…”
Section: Clinical Representationmentioning
confidence: 99%
“…Placebo‐controlled studies can also complement observational methods, allowing assessment of causal effects of cannabis exposure in different age groups. Indeed, we recently showed contrasting patterns of acute cannabis effects in adolescent and adult cannabis users . Specifically, adolescents experienced blunted intoxication and memory effects of cannabis, offering preliminary evidence that adolescents may be resilient to some acute effects of cannabis.…”
mentioning
confidence: 89%
“…For example, even though human research is still in its infancy, experimental studies indicate preliminary evidence that cannabidiol may protect against the negative effects of delta‐9‐tetrahydrocannabinol (∆9‐THC) on cognition , psychotic symptoms and anxiety . Interestingly, a recent within‐subject placebo‐controlled study in human adolescents and adults showed preliminary evidence for both adolescent resilience (blunted subjective, memory, physiological and psychotomimetic effects) and vulnerability (lack of satiety and impaired inhibition) to the direct effect of cannabis (12% THC, < 1% cannabidiol) . Moreover, a study investigating psychophysical effects in frequent and occasional cannabis users following placebo, smoked, vaporized and oral THC administration showed preliminary evidence for an interaction between use history and route of administration, such that impairments were more prolonged following an oral dose, specifically in occasional cannabis users .…”
Section: Report Overviewmentioning
confidence: 99%